Analisis Kinerja Keuangan Menggunakaan Analisa Rasio Keuangan pada Bank Jabar Banten (BJB) - Sumarsana, Wikanda; Hernawati, Euis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Good bank performance will influence the bank's health level, which then produces optimal profits. This research aims to analyze the health level of Bank BJB through financial reports, which can then be used for management and assist in decision making. The research was carried out by analyzing the LDR, ROA, ROE, NIM, NPL, BOPO and CAR ratios during the 2018-2022 period. The method used in this research is descriptive qualitative, by identifying trends in problems that occur and then providing a systematic and accurate picture of the relationships, nature and facts that occur. The research results show that the financial ratio value of Bank BJB is in accordance with the standards set by Bank Indonesia, which is shown in the Liquidity ratio through LDR, can be declared Liquid or capable of meeting its short-term obligations. Then, in terms of profitability and solvency ratios, it appears that Bank Jabar Banten has good management quality and capable of managing their finances so that it can produce maximum profits. Overall, Bank Jabar Banten is in a healthy financial position.